Analysis of Changes in Speaking Manners by Mixing Indonesian and English: a Case Study of Generation Z Teenagers - Jatmiko Murdiono; Ainayah Safira Fadillah (MultiTech Publisher, 2023)
The purpose of this research is to examine the actual situation of social phenomena that occur among young people, using Indonesian and English. Today's children, better known as Generation Z, have experienced many significant changes in their increasingly advanced modern evolution. One of these is the communication style of Gen Z children, who are accustomed to using multiple languages. In Indonesia, it is common for everyone to use Indonesian for communication. However, it is very unfortunate that over time, changes have occurred in language styles in society, especially among young people. Today's children, better known as Generation Z, have experienced many significant changes in their increasingly advanced modern evolution. One of these is the communication style of Gen Z children, who are accustomed to using multiple languages. In Indonesia, it is common for everyone to use Indonesian for communication. However, it is very unfortunate that over time, changes have occurred in language styles in society, especially among young people.